Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Un féminisme décolonial - Vergès, Françoise (La fabrique, 2019)
Dans le débat public, être décolonial est une infamie. Dans les universités, dans les partis de gauche et d'extrême gauche, les syndicats, les associations féministes, partout on traque une "pensée décoloniale" infiltrée et funeste pour le vivre-ensemble. Dans ce livre, Françoise Vergès élucide l'objet du scandale. Le féminisme décolonial révèle les impensés de la bonne conscience blanche ; il se situe du point de vue des femmes racisées : celles qui, travailleuses domestiques, nettoient le monde ; il dénonce un capitalisme foncièrement racial et patriarcal. Ces pages incisives proposent un autre récit du féminisme et posent toutes les questions qui fâchent : quelles alliances avec les femmes blanches? Quelle solidarité avec les hommes racisés? Quelles sont les premières vies menacées par le capitalisme racial? Pourquoi les néofascismes s'attaquent-ils aux femmes racisées? Ce livre est une invitation à renouer avec la puissance utopique du féminisme, c'est-à-dire avec un imaginaire à même de porter une transformation radicale de la société.
https://www-cairn-info.proxy.bibliotheques.uqam.ca/un-feminisme-decolonial–9782358721745.htm
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; OFDIG; anticapitalisme; approches et analyses; com5170; cours; cycles supérieurs; europe; fem1000; fem7000; france; féminisme décolonial; har4600; incontournable; justice sociale; lit4700; pol4212; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; théories féministes

Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."–Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
https://oxford-universitypressscholarship-com.proxy.bibliotheques.uqam.ca/view/10.1093/acprof:oso/9780198237907.001.0001/acprof-9780198237907
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie